Professional Development Needs of Community College Administrators - Folberg, Shawn Michael (My University, 2016)
The purpose of this study was to identify professional development needs of community college administrators in relation to the 45 competencies set forth by the American Association of Community Colleges (AACC). Essential competencies set forth by the AACC were classified into Organizational Strategy, Resource Management, Communication, Collaboration, Community College Advocacy, and Professionalism (AACC, 2015c). This study sought to determine whether there was a statistically significant difference in the importance of these competencies for administrative positions at community colleges located in the southeastern United States. Professional development needs, based on these competency categories, were considered when administrators were contemplated as one group and when administrators were categorized according to level of administration, including top-level, middle-level, lower-level educational, and lower-level support staff. Administrators were asked to rate the importance of each competency to their administrative position and to rate their self-perceived level of competence. The data were analyzed using a Friedman test, Wilcoxon signed rank test, and multivariate analysis of variance (MANOVA); triangulation was also conducted with qualitative, open-ended response data. Findings were considered significant at p < .05. The fundamental reasoning was that if a statistically significant difference existed between the self-perceived importance rating and present level of competence of an administrator, based on a weighted discrepancy scoring system and the AACC competency groupings, such discrepancy would serve as a suitable indicator of the need for professional development activities. The major conclusions of this study included (1) administrators were interested in improving their abilities related to certain,selected competencies; (2) several competency areas were identifiable without regard to level of administration, and thus certain professional development needs can be viewed as uniform across all levels of administration; and (3) professional development needs were indicated most often related to organizational strategy, followed in order by resource management, communication, collaboration, and professionalism. Community college advocacy was viewed as least important.
Chapter I: INTRODUCTION 1 Background 1 Statement of the Problem 2 Theoretical Context for the Study 3 Purpose of the Study 9 Research Questions 10 Definition of Terms 11 Research Procedures 12 Methodology 12 Sampling Technique 14 Data Collection Methods 14 Data Analysis Procedures 16 Significance of the Study 18 Limitations and Delimitations of the Study 19 Summary 20 Chapter II: REVIEW OF LITERATURE 21 Introduction 21 History of the Community College 22 Structure of the Community College 25 Administrative Staff Careers 27 Community College Leaders 33 Leadership Theory and Practice 35 Leadership Professional Development Activities 46 Summary 56 Chapter III: METHODOLOGY 59 Research Design 61 Visual Model of Procedures 63 Participants and Setting 64 Instrumentation 64 Reliability and Validity 69 Sampling Strategy 70 Procedures 70 Data Collection and Management 71 Data Analysis 72 Procedures – Research Questions 1 and 2 73 Procedures – Research Question 3 74 Ethical Considerations 74 Summary 75 Chapter IV: RESULTS 76 Demographic Data 76 Missing Data 77 Inferential Statistics 79 Category 1: Organizational Strategy 79 Category 2: Resource Management 81 Category 3: Communication 83 Category 4: Collaboration 85 Category 5: Community College Advocacy 86 Category 6: Professionalism 88 Category Comparison 90 Qualitative Data 98 Chapter V: SUMMARY AND DISCUSSION 104 Summary 104 Discussion 105 Implications 117 Conclusions 119 Recommendations 120 REFERENCES 122 APPENDIX A: Institutional Review Board Exemption Certificate 131 APPENDIX B: Administrative Staff Questionnaire 132 APPENDIX C: Titles of Administrative Staff Members Categorized for Analysis 133 APPENDIX D: Initial E-mail to Prospective Participants 134 APPENDIX E: Follow-up E-mail to Prospective Participants 135 LIST OF TABLES Table 1: Organizational Strategy Weighted Discrepancy Scores per Competency 80 Table 2: Organizational Strategy Results for the Freidman Tests 81 Table 3: Resource Management Weighted Discrepancy Scores per Competency 82 Table 4: Resource Management Results for the Freidman Tests 83 Table 5: Communication Weighted Discrepancy Scores per Competency 84 Table 6: Communication Results for the Freidman Tests 84 Table 7: Collaboration Weighted Discrepancy Scores per Competency 85 Table 8: Collaboration Results for the Freidman Tests 86 Table 9: Community College Advocacy Weighted Discrepancy Scores per Competency 87 Table 10: Community College Advocacy Results for the Friedman Tests 88 Table 11: Professionalism Weighted Discrepancy Scores per Competency 89 Table 12: Professionalism Results for the Freidman Tests 90 Table 13: The Six Categories Weighted Discrepancy Scores 91 Table 14: The Six Categories Results for the Freidman Tests 91 Table 15: Results for the Wilcoxon Sign Ranks Test for All Pairs of Categories 94 Table 16: MANOVA Results with the Six Categories as the Dependent Variables and the Administration Level as the Independent Variable 97
Keywords: Dissertations; Education; Education, Higher